Zeta Integrals of GSp(4) via Bessel Models - Tran, Long (My University, 2019)
Using the Piatetski-Shapiro theory of zeta integrals via Bessel models, we explicitly calculate L-factors of irreducible admissible representations of GSp(4, F), where F is a non-archimedean local field of characteristic zero.
Keywords: Mathematics